Draft Act Regulating the Legal Status of the Catholic Church in Poland, Prepared by the Working Group for Legislation and Submitted in January 1983 to the Joint Commission of Representatives of the Conference of the Episcopate of Poland and the Government of the Polish People’s Republic - Stępień, Marek (Prawo Kanoniczne, 2025)
In 1980, the Polish authorities reaffirmed their intention to normalize relations with the Catholic Church in Poland and to reactivate the Joint Commission composed of representatives of the Government and the Conference of the Episcopate of Poland. Following the resumption of its sessions, the Commission’s work proceeded in a constructive manner. Within the framework of the Joint Commission, several working groups were established, whose work was positively assessed by members of the Joint Commission. During the first two years of activity of the Working Group on Legislation, the content of the draft act on the relationship between the State and the Catholic Church in Poland was agreed and presented to the Joint Commission of representatives of the Polish Episcopal Conference and the government of the Polish People's Republic in January 1983. The proposed act represented a comprehensive attempt to regulate the legal aspects of the mutual relations between the State and the Catholic Church in Poland.